Influence of crystallographic orientations and nanovoid on the plastic mechanism and damage behavior of single-crystal tungsten under shock - Ziyi Li; Wensheng Liu; Yunzhu Ma; Chaoping Liang (Journal of Materials Research and Technology)
In this work, we investigated the shock response of single-crystal tungsten with pre-existing voids using nonequilibrium molecular dynamics simulations, considering four crystallographic orientations ([100], [110], [111], and [112]). The results reveal that the presence of nanovoids significantly reduces the spall strength of tungsten. For perfect single crystals, the spall strength is highest along [111] (47.65 GPa) and [112] (42.89 GPa), while [110] exhibits the lowest value (32.79 GPa). However, with a void radius of 1.644 nm, the spall strength of [111] and [112] decreases sharply to 24.14 GPa and 20.16 GPa, respectively. In contrast, the spall strength reduction is minimal for [100] and [110]. Various plastic deformation mechanisms, such as dislocation emission, twinning, and prismatic loop formation, were observed during shock compression, with distinct differences between perfect and void-containing samples. These mechanisms and the associated microstructural evolution explain the anisotropic spallation behavior and provide insights into the rapid decline in spall strength for specific orientations.